Symbiotic and nonsymbiotic hemoglobin genes of Casuarina glauca. - Jacobsen-Lyon, K (1995)
Casuarina glauca has a gene encoding hemoglobin (cashb-nonsym). This gene is expressed in a number of plant tissues. Casuarina also has a second family of hemoglobin genes (cashb-sym) expressed at a high level in the nodules that Casuarina forms in a nitrogen-fixing symbiosis with the actinomycete Frankia. Both the nonsymbiotic and symbiotic genes retained their specific patterns of expression when introduced into the legume Lotus corniculatus. We interpret this finding to mean that the controls of expression of the symbiotic gene in Casuarina must be similar to the controls of expression of the leghemoglobin genes that operate in nodules formed during the interaction between rhizobia and legumes. Deletion analyses of the promoters of the Casuarina symbiotic genes delineated a region that contains nodulin motifs identified in legumes; this region is critical for the controlled expression of the Casuarina gene. The finding that the nonsymbiotic Casuarina gene is also correctly expressed in L. corniculatus suggests to us that a comparable non-symbiotic hemoglobin gene will be found in legume species.